Use of a plant-based flavonoid blend in diet for growth, nutrient digestibility, gut microbiota, blood metabolites, and meat quality in broilers - Akter, Shathi; Rahman, Md Aliar; Al-Mamun, Mohammad; Siddique, Mahbubul Pratik; Hashem, Md Abul; Chowdhury, Rakhi (Journal of Advanced Veterinary and Animal Research, 2024)
Objectives: This study aimed to determine the optimal doses of a flavonoid blend (FB) for enhancing cost-efficient production, digestibility, gut-beneficial microbiota, serum metabolites, and meat quality in broilers. Materials and Methods: For 35 days, 280-day-old chicks (Cobb-500) were randomly allocated to four groups, each containing 70 birds, with 5 replicates. Birds were given FB (gm/kg) at the levels of 0.0, 0.2, 0.4, and 0.6 in a basal diet (corn-soya-based) and designated as the control, 0.2 FB, 0.4 FB, and 0.6 FB groups, respectively. At 35 days, 15 birds from each group were slaughtered to analyze cecum microbiota, serum profiles, meat, and bone quality. Results: Compared with the control, birds given FB linearly showed better feed intake and overall performance, with the optimum results observed in 0.6 FB. Birds fed FB resulted in linear, quadratic, and cubic improvements in digestibility, with the 0.6 FB group presenting 12% more (p < 0.01) crude protein digestibility than the control. Birds offered either 0.4 FB or 0.6 FB increased (p < 0.01) the population of beneficial bacteria while reducing (p < 0.01) pathogenic bacteria in the cecum compared to the control. Birds fed 0.6 FB showed substantial improvements in beneficial serum metabolites and liver health, along with reduced bad cholesterol compared with the control. Although FB was unaffected (p > 0.05) by dressed yield, meat composition, lightness, or bone characteristics, the 0.6 FB group showed substantially (p < 0.01) more meat redness and bone ash percentage in broilers than in the control. Conclusions: Supplementing 0.6 gm FB/kg of diet improved growth performance, enhanced digestibility, increased beneficial gut microbiota and serum metabolites, and ameliorated meat quality in broilers. J. Adv. Vet. Anim. Res., 11(4): 1-988, December 2024 http://doi.org/10.5455/javar.2024.k848